Why we might be misusing process mass intensity (PMI) and a methodology to apply it effectively as a discovery level metric. Issue 1 (29th November 2019) - Monteith, Edward R.; Mampuys, Pieter; Summerton, Louise; Clark, James H.; Maes, Bert U. W.; McElroy, C. Robert
Abstract : Are the comparisons of PMI values fair and informative, are you making a like versus like assessment? Abstract : Process mass intensity (PMI) is a key mass-based metric to evaluate the green credentials of an individual or sequence of reactions during process and chemical development. The increasing awareness to consider greenness as early as the initial discovery level, requires a set of parameters suitable to assess it at this stage of development, and guidelines to apply them correctly. This paper evaluates when and how PMI can be used in a correct manner. Different simulations for key reactions in the organic synthesis toolbox – i.e. amide bond formation and Mitsunobu reactions – illustrate that PMI can easily be misleading without due consideration of yield, concentration and molecular weight of reactants and product. A fair appraisal of the green potential of different methodologies therefore requires careful analysis of the examples and metrics data generated.